Effect on Workability and Compressive Strength of M40 Grade of Concrete by Partial Replacement of Cement by Nano Tio2 (International Journal of Innovative Research in Engineering & Management, 2022)
TiO2 is one of the most often used  pigment ingredients in paints due to its many benefits.  TiO2 can be used as a filler material in concrete to fill in  cracks, voids, fissures, bleeding channels, and other gaps,  hence increasing the concrete's strength. The goal of the  current work is to examine how well M40 grade high  strength concrete performs when nanomaterials are used.  This has been done by partially substituting nano titanium  dioxide (tio2) for cement (varying from 0.5% to 2%). By  performing the slump cone test and the compaction factor  test, it was possible to compare the workability of M40  grade concrete with and without the addition of nano tio2. Finally, compression, split tensile, and flexural tests have  been used to assess the strength properties of both types  of concrete.
Keywords: Ultraviolet radiation; NanoTio2; and High Strength Concrete